Penerapan Data Mining Untuk Klasifikasi Kualitas Udara di Daerah Istimewa Yogyakarta Menggunakan Algoritma C4.5 - Nur Adiya, Az Zahra Dwi; Desvita, Amanda Fitria; Fidela, Anindya; Amelia, Dwi; Astuti, Tri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Air pollution is a global environmental problem that is of serious concern in various regions around the world, including in Indonesia. Poor air quality has negative impacts on human health, ecosystems and economic growth. The purpose of this research is to classify the air quality in the Special Region of Yogyakarta. Classification is done using data mining techniques with the C4.5 algorithm or decision tree. The results of the analysis that has been studied using the C4.5 algorithm used 5822 data and 20 replacement samples with 100 repetitions, so the results of this study obtained 7 decisions or leaves with a success rate of 99.9485% and a failure rate of 0.0515%.